Flame‐retardant rigid polyurethane foam with a phosphorus‐nitrogen single intumescent flame retardant - Wang, Chao; Wu, Yicheng; Li, Yingchun; Shao, Qian; Yan, Xingru; Han, Cui; Wang, Zhe; Liu, Zhen; Guo, Zhanhu (Polymers for advanced technologies, 2018)
A phosphorous‐nitrogen intumescent flame‐retardant, 2,2‐diethyl‐1,3‐propanediol phosphoryl melamine (DPPM), was synthesized and characterized by Fourier transform infrared spectroscopy and nuclear magnetic resonance. Flame‐retardant rigid polyurethane foams (RPUFs) with DPPM (DPPM‐RPUF) as fire‐retardant additive were prepared. Scanning electron microscope (SEM) and mechanical performance testing showed that DPPM exhibited a favorable compatibility with RPUF and negligibly negative influence on the mechanical properties of RPUF. The flame retardancy of DPPM on RPUF was investigated by the limiting oxygen index (LOI), vertical burning test and cone calorimeter. The LOI of DPPM‐RPUF could reach 29.5%, and a UL‐94 V‐0 rating was achieved, when the content of DPPM was 25 php. Furthermore, the DPPM‐RPUF exhibited an outstanding water resistance that it could still obtain a V‐0 rating after water soaking. Thermogravimetric analysis showed that the residual weight of RPUF was relatively low, while the charring ability of DPPM‐RPUF was improved greatly. Real‐time Fourier transform infrared spectroscopy was employed to study the thermo‐oxidative degradation reactions of DPPM‐RPUF. The results revealed that the flame‐retardancy mechanism of DPPM in RPUF was based on the surface charred layer acting as a physical barrier, which slowed down the decomposition of RPUF and prevented the heat and mass transfer between the gas and the condensed phases.